Community Participation In The Development Of Home Stay At Kacirebonan Palace - Setiawan, Agung; Shabrina, Fitriatunnisa (Jurnal Toursci, 2024)
The current Kacirebonan Palace still exists and continues to make changes along with the development of tourism, making the Kacirebonan Palace one of the attractions of tourist destinations that travelers or tourists must visit. Therefore, tourism activities must be prepared homestay facilities for tourists who come to the Kacirebonan Palace. The research method that will be used includes observation, interviews, and also documentation to find out how community participation in homestay development at the Kacirebonan Palace in implementing and implementing using the criteria recommended in the ASEAN Tourism Strategic Plan (ATSP): 2011-2015 homestay building. The results of the data collection will be descriptive and qualitative. Based on ASEAN Tourism Strategic Plan (ATSP) criteria: 2011-2015 homestay building. The Kacirebona Palace community can develop homestays as tourism products at the Kacirebonan Palace.